DISCRETE EVENT SIMULATION UNTUK ANALISIS PELAYANAN BISNIS KULINER DI MIE BROSKI KOTA KUPANG - Duka, Irene Oktaviani; Sumarlin (Lembaga Pengembangan Kinerja Dosen, 2025)
Discrete Event Simulation (DES) is a modeling method used to analyze service systems by modeling each event as a series of discrete events. This study aims to analyze the efficiency and effectiveness of the service process at Mie Broski, Kupang City, which focuses on customer queue management and service time. DES allows identification of potential in the system and provides recommendations for improvement through simulation of various operational scenarios. Factors such as service time, number of workers, and queuing system are the main variables analyzed in this study. Using observation and interview data, the simulation results show that workforce quartz and queuing system modifications can significantly increase customer satisfaction. The results of this study are to present innovation in the service system at Mie Broski with the application of Discrete Event Simulation (DES) to analyze and optimize the queuing process and service time to improve operational efficiency and effectiveness by modifying the queuing system and workforce management, so that it can handle a larger volume of customers and improve overall service quality. The application of Discrete Event Simulation in this study especially in queue management and service time. system have been proven to be able to significantly increase operational efficiency and customer satisfaction.